THE MIGRATION REGULARITIES OF THE TELEVISION AUDIENCE / ЗАКОНОМЕРНОСТИ МИГРАЦИЙ ТЕЛЕВИЗИОННОЙ АУДИТОРИИ - SHARIKOV A.V. / ШАРИКОВ А.В. (Наука телевидения)
On the basis of opinion polls the article studies the patterns of migration of the audience in TV space— shifting the viewer from channel to channel or within a channel from one essential event to another—and defines quantitative measures of migration: the arrival of the audience, the leaving of the audience, the amount of audience migration, the migration balance of the audience. At the same time in Russia the audience is often practicing continuous television viewing, not its clip style.